“Who Am I” and “What Can They Do”: The Personhood of Artificial Beings and the Futuristic Development of Religion in Posthuman Era - Li, Chang; Huang, Yuwei (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
The challenge posed by technological advancements to religions is a well-established topic. However, the granting of personhood to artificial beings not only amplifies this challenge (what can they do) but also transforms the identity of human beings (who am I). The exploration of granting personhood to artificial beings by many countries, directly or indirectly, indicates a trend aligned with posthumanism. This article delves into two aspects of transcendence (personhood of artificial beings and identity of human beings) in order to ascertain their impact on religions and its futuristic development.